Prevalence and factors associated with experience of corporal punishment in public schools in South Africa. - Pinky Mahlangu; Esnat Chirwa; Mercilene Machisa; Yandisa Sikweyiya; Nwabisa Shai; Rachel Jewkes (PLoS ONE, 2021)
Background Corporal punishment (CP) is still a common practice in schools globally. Although illegal, studies in South Africa report its continued use, but only a few have explored factors associated with school CP. Moreover, extant studies have not shown the interrelationships between explanatory factors. This study aimed to determine the prevalence and factors associated with learners' experiences, and to examine pathways to the learners' experiences of CP at school. Method 3743 grade 8 learners (2118 girls and 1625 boys) from 24 selected public schools in Tshwane, South Africa, enrolled in a cluster randomised controlled trial evaluating a multi-component school-based intervention to prevent intimate partner violence, and completed self-administered questionnaires. We carried out descriptive analysis, simple linear and structural equation modelling to examine factors and pathways to the learners' experience of CP at school. Results About 52% of learners had experienced CP at school in the last 6 months. It was higher among boys compared to girls. Experience of CP at school amongst learners was associated with learner behavior, home environment, and school environment. Learners from households with low-socio economic status (SES) had an increased risk of CP experience at school. Amongst boys, low family SES status was associated with a negative home environment and had a direct negative impact on a learner's mental health, directly associated with misbehavior. Conclusion CP in public schools in South Africa continues despite legislation prohibiting its use. While addressing learner behaviour is critical, evidence-based interventions addressing home and school environment are needed to change the culture among teachers of using corporal punishment to discipline adolescents and inculcate one that promotes positive discipline.